Paradiplomacy and Its Influence on Visitor Trends at Twin World Heritage Sites: A Case Study of Borobudur Temple 2018-2019 - Lailatul Lufiah; Gumantiara, Miftah Ichwani; Zaky Ramadhan (Journal of Paradiplomacy and City Networks, 2024)
Indonesia, recognized for its substantial tourism potential, has leveraged the iconic Borobudur Temple, a premier cultural heritage site, to bolster its international cultural diplomacy and marketing efforts. This study examines the impact of the Twin World Heritage cooperation program implemented by the Indonesian government through PT. Taman Wisata Candi, on visitor numbers at Borobudur Temple during 2018-2019. The program epitomizes a strategic approach to enhancing cultural relations by facilitating cross-border collaborations and the exchange of expertise in cultural preservation and promotion. Situated in Magelang, Central Java, the Twin World Heritage Program at Borobudur Temple has not only elevated the temple's global profile but has also served as a pivotal instrument in strengthening international cultural ties and fostering mutual appreciation and understanding across nations. The empirical data from this study reveal a notable increase in visitor attendance: domestic visitor figures rose from 3,663,054 in 2018 to 3,747,757 in 2019, while foreign visitor numbers increased from 192,231 to 242,082 over the same period. These findings affirm the program's efficacy in harnessing Borobudur's potential and generating significant socio-economic benefits across multiple sectors.